An Influence of Price and Ease of Purchasing on Tokopedia e-commerce on Consumer Satisfaction during the Covid19 Pandemic - Melani Quintania; Monica Naomi Julyana Banjarnaho (Sultan Publisher, 2024)
The number of COVID–19 cases in Indonesia, which continues to show a significant increase, requires the Government to issue physical distancing and social distancing policies. One of the ways that people do to minimize leaving their homes is by shopping online. The ease of purchase factor specifically dominates consumer satisfaction shopping online. This study verifies the effect of price and ease of purchase on E-commerce Tokopedia on consumer satisfaction, either partially or simultaneously. The kind of research used is causality with a quantitative analysis approach. The sampling technique was taken by selecting the subject based on the specific criteria that had been determined, namely the respondent's domicile the number of purchases in the last six months. The number of samples set in this study was 100 respondents. Multiple regression analysis was used in this study, starting with testing the validity of the data and testing the classical assumptions. Research on consumer satisfaction in E-commerce Tokopedia is known that the price factor has a strong enough affect on consumer satisfaction; the effect of ease of purchase is also influential on consumer satisfaction. This study suggests that companies formulate competitive and affordable pricing for consumers, maintain price stabilization, and provide clear information regarding the convenience of shopping at Tokopedia, especially for new consumers.